Systematic evaluation of a panel of 30 synthetic cannabinoid receptor agonists structurally related to MMB‐4en‐PICA, MDMB‐4en‐PINACA, ADB‐4en‐PINACA, and MMB‐4CN‐BUTINACA using a combination of binding and different CB1 receptor activation assays. Part III: The G protein pathway and critical comparison of different assays. Issue 7 (21st May 2021) - Grafinger, Katharina Elisabeth; Vandeputte, Marthe M.; Cannaert, Annelies; Ametovski, Adam; Sparkes, Eric; Cairns, Elizabeth; Juchli, Patrick Osamu; Haschimi, Belal; Pulver, Benedikt; Banister, Samuel D.; Stove, Christophe P.; Auwärter, Volker
Abstract: The present work is the last of a three‐part study investigating a panel of 30 systematically designed synthetic cannabinoid receptor agonists (SCRAs) including features such as the 4‐pentenyl tail and varying head groups including amides and esters of l ‐valine (MMB, AB), l ‐ tert ‐leucine (ADB), and l ‐phenylalanine (APP), as well as adamantyl (A) and cumyl moieties (CUMYL). Here, we evaluated these SCRAs for their capacity to activate the human cannabinoid receptor 1 (CB1 ) via indirect measurement of G protein recruitment. Furthermore, we comparatively evaluated the results obtained from three in vitro assays, based on the recruitment of β‐arrestin 2 (βarr2 assay) or Gαi protein (mini‐Gαi assay), or binding of [ 35 S]‐GTPγS. The observed efficacies ( E max ) varied depending on the conducted assay. Statistical analysis suggests that the population means of the relative intrinsic activity (RAi ) significantly differ for the [ 35 S]‐GTPγS assay and the other two assays, but the population means of the βarr2 and mini‐Gαi assays were not statistically different. Our data suggest that differences observed between the βarr2 and mini‐Gαi assays are the best predictor for 'biased agonism' towards βarr or G protein recruitment in our study. SCRAs carrying an ADB or MPP moiety as a head group tended to produce elevated E max values in the βarr2 assay, which might result in a tendency of these compounds to cause pronounced tolerance in users—a hypothesis that should be evaluated further by future studies. In general, a comparison of efficacies derived from different assays is difficult and should only be conducted very cautiously. Abstract : This work presents an investigation of a panel of 30 SCRA analogues for their human cannabinoid 1 receptor (CB1) activity via two different G protein recruitment assays. Furthermore, a comparative evaluation of the results was obtained from three in vitro assays, based on the recruitment of β‐arrestin 2 (βarr2 assay) (Part II) or Gαi protein (mini‐Gαi assay), or binding of [ 35 S]‐GTPγS. The chemical synthesis and characterization presented of the 30 test compounds was presented in Part I of this study. ​